Highly Efficient Terahertz Generation Using 3D Dirac Semimetals. Issue 10 (20th July 2022) - Wang, Lu; Lim, Jeremy; Wong, Liang Jie
Abstract: It is shown that three‐dimensional Dirac semimetals are promising candidates for highly efficient optical‐to‐terahertz conversion due to their extreme optical nonlinearities. In particular, it is predicted that the conversion efficiency of Cd 3 As 2 $\text{Cd}_{\text{3}}\text{As}_{\text{2}}$  exceeds typical materials like LiNbO 3 $\text{LiNbO}_{\text{3}}$  by >5000 times over nanoscale propagation distances. Studies show that even when no restrictions are placed on propagation distance, Cd 3 As 2 $\text{Cd}_{\text{3}}\text{As}_{\text{2}}$  still outperforms LiNbO 3 $\text{LiNbO}_{\text{3}}$  in efficiency by >10 times. The results indicate that by tuning the Fermi energy, Pauli blocking can be leveraged to realize a step‐like efficiency increase in the optical‐to‐terahertz conversion process. It is found that large optical‐to‐terahertz conversion efficiencies persists over a wide range of input frequencies, input field strengths, Fermi energies, and temperatures. These results could pave the way to the development of ultrathin‐film terahertz sources for compact terahertz technologies. Abstract : Due to their extreme optical nonlinearity, three‐dimensional Dirac semimetals are promising candidates for highly efficient optical‐to‐terahertz conversion, that is, 5000 times more than lithium niobiate, over nanoscale propagation distances. The large conversion efficiencies persist over a wide range of input frequencies, input field strengths, Fermi energies, and temperatures. These results could pave the way to compact terahertz technologies.